A Corpus-Based Study of High-Frequency Words in Madurese Textbooks for Elementary School - Zakiyah, Fitriyatuz; Susylowati, Eka (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to analyze high-frequency words used in Madurese language textbooks for grade 4th, 5th, and 6th of elementary school students. The data in this study is a corpus created from two Madurese language textbooks for elementary schools used in grade 4th, 5th, and 6th in Bangkalan. The data was processed using concordance software, namely Lancsbox, to identify the vocabulary that are frequently used in those textbooks. Then, the data was analysed qualitatively to know the meaning and the word classes of the words. The results of this study show that the frequency of words that are most often used in textbooks in the three classes is the same, those are and “sè” which mean